ECONOMICS LEARNING THAT INTEGRATES ANTI-CORRUPTION VALUES IN HIGH SCHOOL TO DEVELOP STUDENT CHARACTER - Surhayanti, Surhayanti; Wahjoedi, Wahjoedi; Wahyono, Hari; Sri Andayani, Endang (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Economic activity or behavior is a reflection of the knowledge and understanding of economics that has been obtained through the learning process, especially economic learning at formal educational institutions. The economic learning material that takes place in formal educational institutions, both from theoretical and practical studies, has experienced a shift in values, namely from values or principles that are in accordance with the Indonesian nation's identity towards teaching the principles of capitalist economics (classical and neoclassical) as the main thing. Ideally, economic education taught in schools instills character values in students, so that the economic behavior carried out can prevent acts of corruption, so it is important to instill anti-corruption values through economics subjects for students. Anti-corruption is an effort to carry out preventing acts of corruption with various efforts to increase individual awareness so that they do not commit acts of corruption, as well as efforts to improve the morale of Human Resources. A review protocol was developed and electronic search strategies were guided by a librarian experienced in systematic and scoping reviews. The Nine Values were introduced by the Corruption Eradication Commission (KPK), as effective moral values in providing a doctrine of anti-corrupt behavior. Values that can be instilled in anti-corruption learning in economics include: (honesty, discipline, caring, responsibility, hard work, and simplicity).